2023
DOI: 10.1002/advs.202205525
|View full text |Cite
|
Sign up to set email alerts
|

Novel Human Meningioma Organoids Recapitulate the Aggressiveness of the Initiating Cell Subpopulations Identified by ScRNA‐Seq

Abstract: High-grade meningioma has an unsatisfactory outcome despite surgery and postoperative radiotherapy; however, the factors driving its malignancy and recurrence remain largely unknown, which limits the development of systemic treatments. Single-cell RNA sequencing (scRNA-Seq) technology is a powerful tool for studying intratumoral cellular heterogeneity and revealing the roles of various cell types in oncogenesis. In this study, scRNA-Seq is used to identify a unique initiating cell subpopulation (SULT1E1 + ) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 76 publications
0
1
0
Order By: Relevance
“…H&E staining and immunostaining against SSTR2A (meningioma cells), CD31 (blood vessels), CD68, and CD3 (immune cells) were performed, as well as an extensive study utilising whole-exome sequencing and scRNA-seq to investigate the cellular heterogeneity within organoids. All these studies demonstrated that meningioma organoids recapitulated the gene expression, mutations, histological features, and cell populations (tumour cells, endothelial cells, tumour-infiltrating macrophages, and T lymphocytes) of the parental tumours [68]. They also identified a SULT1E1 + subpopulation within parental tumours, which was implicated in the progression of meningiomas to a higher grade.…”
Section: Organoids To Model Meningiomamentioning
confidence: 82%
See 3 more Smart Citations
“…H&E staining and immunostaining against SSTR2A (meningioma cells), CD31 (blood vessels), CD68, and CD3 (immune cells) were performed, as well as an extensive study utilising whole-exome sequencing and scRNA-seq to investigate the cellular heterogeneity within organoids. All these studies demonstrated that meningioma organoids recapitulated the gene expression, mutations, histological features, and cell populations (tumour cells, endothelial cells, tumour-infiltrating macrophages, and T lymphocytes) of the parental tumours [68]. They also identified a SULT1E1 + subpopulation within parental tumours, which was implicated in the progression of meningiomas to a higher grade.…”
Section: Organoids To Model Meningiomamentioning
confidence: 82%
“…Spheroids can be cultivated with or without growth factors, whereas organoids must be cultured with specific factors [60]. However, spheroids can be formed within 24 h, whereas organoids take longer to form, ranging from weeks to months [55,60,68,69].…”
Section: Differences Between Organoids and Spheroidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transcriptional analysis of GBM organoids revealed possible ligand-receptor interactions between tumor and organoid cells [22]. Huang et al developed an organoid model for meningioma, and immunohistochemistry analysis revealed striking similarities in cellular heterogeneity between meningioma patient samples and meningioma organoids, which include tumor cells, T-lymphocytes, macrophages, and vascular endothelial cells [23]. However, high-cost, complex model development protocols, lack of proper vasculature, and poor controllability limit the applications and clinical implications of these models [24].…”
Section: In Vitro Models For Pediatric Cancersmentioning
confidence: 99%